Malay women's responses to a changing world: a feminist postcolonial reading of Ellina binti Abdul Majid's Perhaps in Paradise - Ibrahim, Syazliyati; Nordin, Razanawati; Adzmi, Nor Aslah; Jusoff, Kamaruzaman (Canadian Academy of Oriental and Occidental Culture, 2009)
Malay women play multiple roles not only in the family but they are also very much connected to their surroundings. One of the dynamics in their surroundings includes political decisions which would inevitably leave marks on the Malay women themselves. Based on such a premise, this paper aims to investigate how the female characters in the novel Perhaps in Paradise respond to the socio-political changes occurring in their milieu. The novel is chosen since it represents the lives of privileged middle class Malay women beginning in the late 1960s who undergo various changes as a result of what happened in Malaysia at that time. This novel which is penned by Ellina binti Abdul Majid is studied by engaging the feminist postcolonial theory. The analysis uncovers that the female characters’ lives in the novel are governed by the hegemonic practices of tradition and religion. Despite the changes which usurp their lives particularly in terms of westernisation and consumerism, they cannot escapefrom the identity which labels them as Malay. At times the characters are subordinated when they succumb to such practices. On the other hand, in certain cases when they retaliate and choose to look to the west for liberation, they could actually be marginalised in their own society. At other times, the cultures of east and west can be negotiated to provide meaningful lives to the characters.